An experimental study on the corrosion susceptibility of Recycled Steel Fiber Reinforced Concrete - Frazão, Cristina (2019)
Steel fibers resulting from the industry of tire recycling can be efficiently employed in concrete to improve its mechanical performance, such as post-cracking load bearing and energy absorption capacity. Under chloride attack, an important aspect of Recycled Steel Fiber Reinforced Concrete (RSFRC) durability is its corrosion resistance. However, the insufficient knowledge on this domain contributes for a conservative design philosophy, which can compromise the cost competitiveness of RSFRC and prevent its application in elements where this occurrence, even eventual, is not acceptable. In the present work, an experimental program was performed with the aim of assessing the corrosion susceptibility of RSFRC including the characterization of the micro-mechanical properties and the corrosion resistance of recycled steel fiber (RSF) by means of nano-indentation testing, electrochemical monitoring techniques and scanning electron microscopy (SEM) analysis. The influence of the small rubber debris attached to the RSF surface was also analyzed by using two distinct pre-treatment methods. The adhesive bond behavior between the RSF and the surrounding self-compacting concrete (SCC) matrix was analyzed by performing monotonic RSF pullout tests. Double edge wedge splitting (DEWS) tests were conducted for evaluating the corrosion effects on the post-cracking response of RSFRC.